INTELLECTUALIZATION OF MONITORING VEHICLES BASED ON THE USE OF PRECEDENTS - Pavlenko, V.; Павленко, В. М.; Павленко, В. М. (Харьковский национальный автомобильно-дорожный университет, 2016)
The article deals with the intellectualization process of vehicle monitoring through the use of decision support systems for diagnostics of technical condition of vehicles on the basis of prece-dents. A generalized architecture of a tool program complex to seek solutions on the basis of precedents is proposed. A tool design precedents library is used in intelligent decision support system prototype solutions to meet the challenges of expert diagnosis and operative management of complex objects.
ІНТЕЛЕКТУАЛІЗАЦІЯ ПРОЦЕСІВ МОНІТОРИНГУ ТРАНСПОРТНИХ ЗАСОБІВ НА ОСНОВІ ВИКОРИСТАННЯ ПРЕЦЕДЕНТІВ
ИНТЕЛЛЕКТУАЛИЗАЦИЯ ПРОЦЕССОВ МОНИТОРИНГА ТРАНСПОРТНЫХ СРЕДСТВ НА ОСНОВЕ ИСПОЛЬЗОВАНИЯ ПРЕЦЕДЕНТОВ
Keywords: vehicle; operator; system of decision support; diagnosis; expert; precedent; library of precedents; intelligent systems; CBR-cycle; транспортний засіб; система підтримки прийняття рішень; діагностика; прецедент; бібліотека прецедентів; транспортное средство; система поддержки принятия решений; диагностика; прецедент; библиотека прецедентов; 629.113